Fitness Costs and Variation in Transmission Distortion Associated with the Abnormal Chromosome 10 Meiotic Drive System in Maize. Issue 1 (1st January 2018) - Higgins, David M; Lowry, Elizabeth G; Kanizay, Lisa B; Becraft, Philip W; Hall, David W; Dawe, R Kelly
Abstract: The maize abnormal chromosome 10 (Ab10) meiotic drive system causes its own preferential transmission through females, yet it is found at low frequencies... Meiotic drive describes a process whereby selfish genetic elements are transmitted at levels greater than Mendelian expectations. Maize abnormal chromosome 10 (Ab10) encodes a meiotic drive system that exhibits strong preferential segregation through female gametes. We performed transmission assays on nine Ab10 chromosomes from landraces and teosinte lines and found a transmission advantage of 62–79% in heterozygotes. Despite this transmission advantage, Ab10 is present at low frequencies in natural populations, suggesting that it carries large negative fitness consequences. We measured pollen transmission, the percentage of live pollen, seed production, and seed size to estimate several of the possible fitness effects of Ab10. We found no evidence that Ab10 affects pollen transmission, i.e., Ab10 and N10 pollen are transmitted equally from heterozygous fathers. However, at the diploid (sporophyte) level, both heterozygous and homozygous Ab10-I-MMR individuals show decreased pollen viability, decreased seed set, and decreased seed weight. The observed fitness costs can nearly but not entirely account for the observed frequencies of Ab10. Sequence analysis shows a surprising amount of molecular variation among Ab10 haplotypes, suggesting that there may be other phenotypic variables that contribute to the low but stable equilibrium frequencies.